Efektivitas Penagihan Tunggakan Pajak dengan Surat Teguran dan Surat Paksa Pada Kantor Pelayanan Pajak (KPP) Madya Palembang - Mursalin Mursalin (JEMBATAN (Jurnal Ekonomi, Manajemen, Bisnis, Auditing, dan Akuntansi), 2019)
This study aims to determine the effectiveness of billing Tax Arrears with Reprimand and Forced Letter at the Palembang Tax Office (KPP). Observed data are the number of Warning Letter, Forced Letter, and the target and realization of tax revenue from 2014 to 2017 at the Palembang Madya Tax Service Office (KPP). The results showed that tax collection with reprimand in the Palembang KPP Madya in 2014 to 2017 when viewed in terms of letter sheets is classified as quite effective while in terms of nominal classified as effective, whereas Tax Collection by Forced Letters at the Palembang Madya Tax Office (KPP) in 2014 to 2017 is considered quite effective both in terms of the number of sheets of the Forced and nominal listed in the Forced Letter.